Risky teachers: mitigating risk through high-stakes teacher evaluation in the USA. Issue 3 (4th May 2019) - Holloway, Jessica
ABSTRACT: As a post-structural critique of US teacher evaluation policy, this paper aims to disrupt accepted conceptualizations of teachers by (1) identifying discursive constructions of teachers in political talk, action, and legislation; (2) unpacking the ways that these constructions operate to legitimize punitive accountability policies and practices; and (3) mapping the associated accountability practices used by one school district to understand how they function to manage teachers and shape teacher subjectivities. Drawing on data that include official federal- and state-level policy documents, policy supplemental materials, and local teacher evaluation materials, this analysis demonstrates how teachers have been discursively positioned as 'risky' subjects. By doing so, the means to mitigate such 'risks' are rationalized, insofar as high-stakes accountability policies and practices 'make sense' to protect the well-being of students and the country. This has enabled a set of intrusive and punitive mechanisms that assess and discipline teachers to behave as low-risk subjects.